MicroRNA Mediated Cardioprotection – Is There a Path to Clinical Translation? - Nazari-Shafti, Timo Z.; Exarchos, Vasileios; Biefer, Héctor Rodriguez Cetina; Cesarovic, Nikola; Meyborg, Heike; Falk, Volkmar; Emmert, Maximilian Y. (Frontiers in Bioengineering and Biotechnology, 2020)
In the past 20 years there have been several approaches to achieve cardioprotection or cardiac regeneration with a vast pallet of first and second generation progenitor cells. To date, substantial proof that these cells have the potential for clinically relevant cardiac repair or regeneration of cardiac tissue is still pending. Preclinical trials indicate that the secretome of these cells may exhibit cardioprotective properties in the acute setting of cardiac injury. The secretome of progenitor cells generally consists of cell-specific cytokines and exosomes containing mircoRNAs (miRNAs). It is currently hypothesized that a subset of known miRNAs are crucial to the cardioprotective effect of progenitor cells. MiRNAs are small non-coding RNA molecules that inhibit post-transcriptional translation of messengerRNAs (mRNAs) and play an important role in gene translation regulation. It is also known that one miRNAs usually targets multiple mRNAs. This makes predictability of pharmacokinetics and mechanism of action very difficult and could in part explain the inferior performance of various progenitor cells in clinical studies. The miRNA profile found in the secretome not been in depth analyzed yet. Therefore, it is possible that the heterogeneous results from these trials are in part explained by varying secretome profiles. Identification of miRNAs involved in cardioprotection and remodeling, the composition of miRNA profiles, and the exact mechanism of action are important to the design of future cell-based but also cell-free cardioprotective therapeutics. This review will give a description of microRNA with cardioprotective properties and a current overview on known mechanism of action and potential missing links. Additionally, we will give an outlook on the potential for clinical translation of mircoRNAs in the setting of myocardial infarction and heart failure.